On the Bridges: Insight Into the Current and Future Use of Automated Systems as Seen by Royal Navy Personnel. (September 2019) - Barrett-Pink, Chloë; Alison, Laurence; Maskell, Simon; Shortland, Neil
This paper explores the current state of automated systems in the Royal Navy (RN), as well as exploring where personnel view systems would have the most benefit to their operations in the future. In addition, personnel's views on the current consultation process for new systems are presented. Currently serving RN personnel ( n = 46) completed a questionnaire distributed at the Maritime Warfare School. Thematic analysis was conducted on the 5, 125 words that were generated by personnel. Results show that RN personnel understand the requirement to utilize automated systems to maintain capability in the increasingly complex environments they face. This requirement will increase as future warfare continues to change and increasingly sophisticated threats are faced. However, it was highlighted that current consultation and procurement procedures often result in new automated systems that are not fit for purpose at time of release. This has negative consequences on operator tasks, for example by increasing workload and reducing appropriate system use, as well as increasing financial costs associated with the new systems. It is recommended that an increase in communication and collaboration between currently serving personnel and system designers may result in preventing the release of systems that are not fit for purpose.